Syndrome of inappropriate anti-diuretic hormone in Kawasaki disease - Mori, Jiro; Miura, Masaru; Shiro, Hiroyuki; Fujioka, Kenichiro; Kohri, Takeo; Hasegawa, Tomonobu (Pediatrics international, 2011)
Background:  The pathogenesis of hyponatremia in acute Kawasaki disease (KD) remains unclear. A recent case report of KD complicated by syndrome of inappropriate anti‐diuretic hormone (SIADH) led us to determine the prevalence of SIADH in acute KD patients. Methods:  Subjects were 39 Japanese KD patients (2–84 months of age, 25 males and 14 females) treated with intravenous immunoglobulin (IVIG), 2 g/kg/day and oral aspirin. SIADH was defined when hyponatremic patients (serum sodium concentration <135 mEq/L) had decreased serum osmolality <280 mOsm/kg H2O, elevated urine sodium concentration >20 mEq/L and elevated urine osmolality >100 mOsm/kg H2O without dysfunctions of renal, thyroid or adrenal gland. We also studied the relation between clinical course of SIADH and the amount of infused fluid during IVIG. Results:  Before IVIG, 27 patients (69%) had hyponatremia and 11 (28% of total; 41% of hyponatremic patients) had SIADH while after IVIG, 13 (33%) hyponatremia and four (10%; 31% of hyponatremic patients) SIADH. Among 11 patients with SIADH before IVIG, SIADH improved in 10 after IVIG, but hyponatremia persisted in five. Significant correlation was observed between serum sodium concentration after IVIG and infusion amount in SIADH patients (r=−0.64, P= 0.03), but not in non‐SIADH patients. Conclusions:  This is the first report to show that SIADH is common as a cause of hyponatremia in acute KD and hence careful management of water and sodium is warranted.